Axial crushing of fiber filled thin tubes - Amzatul Akmam, Mokhtar; Md. Radzai, Said (2006)
The energy absorption capacity of a series of axially crushed tubes filled with oil palm fiber is compared with empty tube. This is to determine the viability of considering the use of such composites or bimaterials in transportation system especially in automotive application. The cross-sectional of tubes are square and rectangular in shape. The tubes arefilled with Empty Fruit Bunch (EFB)fibers and with Oil Palm Frond (OPF) fibers; and some of them were added with water or urea formaldehyde. The fibers densities are ranging from 150 kgm-3 to 300 kgm-3 . It was also found that the rectangular mild steel tubes filled with 300 kgm-3 Oil Palm Frond fiber was good in absorbing energy compared with others densities.